Asymptomatic Dandy Walker malformation in an elderly male with acute haemorrhagic stroke – a case report - Minhaj, Areeba; Minhaj, Marium; Farooqui, Muhammad Osama; Naseeb, Muhammad Wahdan; Hafiz Muhammad Saad; Shaheen Bhatty (Journal of the Pakistan Medical Association, 2023)
Dandy-Walker Malformation (DWM) is a rare congenital anomaly of the posterior cranial fossa. Features of DWM include hypoplasia of the cerebellar vermis, enlargement of the posterior fossa, and cystic dilatation of the fourth ventricle. MRI is the modality to confirm the diagnosis. Treatment is usually symptomatic and required when signs of hydrocephalus develop. Rare cases of asymptomatic DWM diagnosed incidentally are reported in literature. We report a case of DWM in a 60-year-old male who presented with haemorrhagic stroke and was later found to have DWM on brain imaging. Keywords: Dandy-Walker Malformation, Haemorrhagic Stroke.